All Days 2012
DOI: 10.2118/150215-ms
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Monitoring of Thermal EOR at Schoonebeek for Intelligent Reservoir Management

Abstract: Time-lapse seismic has shown many successful offshore applications, but has turned out to be much more cumbersome when applied onshore. Successful applications are mainly observed for shallow objectives and large acoustic impedance changes, such as thermal EOR and CO2 injection. The dominant problems for onshore time-lapse are caused by near-surface variations between base and monitor surveys [Pevzner 2011]. By taking appropriate measures in acquisition and processing it is possible to overcome these problems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The source and receiver lines are located such that they are right above the point where the two observation wells intersect the reservoir. J.C. Hornman et al (2012) and J. Cotton et al (2012) showed that quantitative time shifts and qualitative amplitude variations, calculated by crosscorrelation on the seismic data, fit with the observation, production and injector well data.…”
Section: Introductionmentioning
confidence: 75%
“…The source and receiver lines are located such that they are right above the point where the two observation wells intersect the reservoir. J.C. Hornman et al (2012) and J. Cotton et al (2012) showed that quantitative time shifts and qualitative amplitude variations, calculated by crosscorrelation on the seismic data, fit with the observation, production and injector well data.…”
Section: Introductionmentioning
confidence: 75%
“…As explained by Hornman et al . (), the travel‐time variations depend on pressure, temperature, gas saturation, and steam. All of these parameters can have constructive or destructive effects.…”
Section: Discussionmentioning
confidence: 99%
“…With such a buried continuous-monitoring system we have been able to track reliably, and in real time, very small reservoir changes (time shifts of a few microseconds; Hornman et al, 2012, Hornman andForgues, 2013). However, the cost of the system is an order of magnitude too high to be attractive for wide-spread application onshore.…”
Section: Onshorementioning
confidence: 99%